Trends in prevalence and incidence of diabetes mellitus from 2005 to 2014 in Taiwan - Sheen, Yi-Jing; Hsu, Chih-Cheng; Jiang, Yi-Der; Huang, Chien-Ning; Liu, Jia-Sin; Sheu, Wayne Huey-Herng (Journal of the Formosan Medical Association, 2019)
Diabetes mellitus (DM) and DM-related complications place a high socioeconomic burden on individuals and society. Updating nationwide information periodically is thus pivotal to preventing DM and improving its management in Taiwan. We used the National Health Insurance Research Database; disease diagnosis codes were assigned according to the International Classification of Diseases, 9th Revision, Clinical Modification. DM was defined as ≥3 outpatient visits or 1 hospitalization within a year. We excluded individuals with gestational DM, those with missing data, and those aged >100 years. Type 1 DM (T1DM) was defined based on information from the catastrophic illness registry. From 2005 to 2014, total population with DM increased by 66% and age-standardized prevalence in patients aged 20–79 years increased by 41%. The DM prevalence was generally higher in men; however, the prevalence was higher in women aged ≥65 years. The prevalence of DM was approximately 50% in those aged >80 years. DM incidence increased by 19%; the increase was most obvious in patients aged 20–39 years (p < 0.001). The standardized incidence of T1DM slightly decreased by 11% (p = 0.118) and standardized prevalence of T1DM increased from 0.04% to 0.05%. Number of T1DM accounted for 0.51–0.59% of the entire diabetic population during the observation period. DM prevalence is continually increasing, but the incidence only marginally increased from 2005 to 2014. Moreover, DM is a major problem in elderly people. The higher incidence of DM in men is consistent with the pandemic of overweight and obesity in men in Taiwan.